PENGARUH FAKTOR PSIKOLOGI TERHADAP PENGAMBILAN KEPUTUSAN INVESTASI SAHAM DIBURSA EFEK INDONESIA (STUDI PADA BURSA EFEK PERWAKILAN SULAWESI TENGGARA) - Indra Dwi Zakiyah; Buyung Sarita; Salma Saleh (Pascasarjana Universitas Halu Oleo, 2022)
The purpose of this study was to determine the effect of investor psychology on investment decisions. The sample of respondents in this study was 100 sampel and actively invested in the Indonesia Stock Exchange (IDX) Representative of Southeast Sulawesi and joined the RHB, IPOT, Phintraco and MNC securities groups. The sampling technique used was the cluster sampling method. The analysis used is quantitative analysis using multiple linear regression analysis and quantitative data processing using SPSS 26.0. The results show that herding, overconfidence, availability bias, regret bias aversion have a positive and significant effect on investment decisions, meaning that the higher the four variables above, the decision to invest will increase. On the other hand, conservatism has a negative and insignificant effect on investment decisions, meaning that when conservatism increases, the decision to invest decreases and vice versa.